A community-based iron supplementation program, "Iron-Like Turkey", and the following prevalence of anemia among infants aged 12-23 months - Yalçın, S. Songül; Tezel, Başak; Yurdakök, Kadriye; Pekcan, Gülden; Ozbaş, Sema; Köksal, Eda; Tunç, Bahattin; Şahinli, Selvi; Altunsu, A. Tanju; Köse, M. Rifat; Buzgan, Turan; Akdağ, Recep (The Turkish Journal of Pediatrics, 2013)
During the second year of the "Iron-like Turkey" Project, in which all children aged 4-6 months in Turkey receive iron supplementation for 5 months, we aimed to assess the utilization of iron supplementation in the field, as well as the prevalence of anemia in healthy infants aged 12-23 months, while determining a variety of sociodemographic and nutritional factors for anemia in three of the 12 NUTS (Nomenclature of Territorial Units for Statistics) regions (regions with the highest, lowest and middle under-5 malnutrition levels). In a community-based, cross-sectional survey using a multi-staged, weighted, cluster-selected sample, children aged 12-23 months with birthweight ≥2500 g, no chronic illness, no history of blood disease, and from term and singleton pregnancy were enrolled; 1589 children met the criteria. The mean±SD age of children surveyed was 17.8±3.6 months. Of the parents, 72.4% claimed that their physician had recommended iron supplementation, and 68.8% had given supplementation to their children. Overall prevalence of anemia was 7.3%. Multivariate analysis revealed that the frequency of anemia decreased significantly in older infants, when supplementation was recommended by health providers, when an infant was breastfed longer than 6 months, and when the mother received iron supplementation during pregnancy. However, anemia prevalence increased when the infant received iron supplementation at a later age (39 months), lived in a crowded family (36 persons), and when the mother had a history of iron deficiency anemia. Anemic infants had significantly lower z scores of weight for age than non-anemic ones. This survey suggests that iron supplementation during pregnancy, initiation of iron supplementation in infants at 4-6 months of age, effective counseling on supplementation, subsequent compliance, support of breastfeeding, and effective training of health care personnel are effective strategies for prevention of anemia in the community.